Getting published in the life sciences - Gladon, Richard J.; Graves, William R.; Kelly, James Michael (Hoboken, N.J. : Wiley-Blackwell, 2011)
"The goal of this book is to make it easier for scientists, especially those new to scientific writing, to write about their results and to get their manuscripts accepted in peer-reviewed journals. The book covers each step throughout the submission process, from organizing and outlining the manuscript, presenting statistical data and results, to what happens during the in-house manuscript review process and what to do if an article is initially rejected. In addition to providing practical exercises on these topics, the book focuses on helping writers distil their research into concise take-home messages for readers, in order to convey information as clearly as possible to the target audience"--
"The goal of this book is to make it easier for scientists, especially those new to scientific writing, to write about their results and to get their manuscripts accepted in peer-reviewed journals. The book covers each step throughout the submission process, from organizing and outlining the manuscript, presenting statistical data and results, to what happens during the in-house manuscript review process and what to do if an article is initially rejected"--
Machine generated contents note: Preface. -- Section I. Preliminary Considerations. -- Chapter 1 The Importance of and Need for Publishing. -- Chapter 2 Steps in Manuscript Preparation and Getting Started. -- Chapter 3 Ethical Issues in Publishing. -- Chapter 4 Choosing Your Coauthors. -- Chapter 5 Choosing Your Journal. -- Chapter 6 Principles and Characteristics of Good Scientific Writing. -- Section II. Development of the Manuscript. -- Chapter 7 Developing the Take-home Messages and a Provisional Title. -- Chapter 8 Organizing and Outlining Your Manuscript. -- Chapter 9 Results I: Overview. -- Chapter 10 Results II: Presentation. -- Chapter 11 Results III: Options for Presenting Results. -- Chapter 12 Results IV: Guidelines for Preparing Written Text of Results. -- Chapter 13 Revising and Editing. -- Chapter 14 References. -- Chapter 15 Materials and Methods. -- Chapter 16 Introduction: Rationale, Review of Literature, and Statements of Objectives. -- Chapter 17 Discussion. -- Chapter 18 Abstract. -- Chapter 19 Title, By-line, Keywords, and Authorship Footnote Items. -- Chapter 20 Polishing Your Manuscript with Good Word Usage: Choice of Words, Misspelled Words, and Misused Words. -- Section III. Review, Submission, and Postsubmission Issues. -- Chapter 21 In-house Manuscript Review Process. -- Chapter 22 Cover Letter and Submission Form Preparation. -- Chapter 23 Final Checklist and Initial Manuscript Submission. -- Chapter 24 The Peer-Review Process of Your Initial Submission. -- Chapter 25 Response-letter Preparation and Manuscript Resubmission. -- Chapter 26 Proofs, Proofreading, and the Final Steps in the Publication Process. -- Appendices. -- Index/Indices.
Keywords: Biology; Authorship; Technical writing; SCIENCE / Life Sciences / Biology / General